APPLICATION OF BARCODING TO MANAGEMENT AND CONSERVATION OF FISH AND THEIR BY-PRODUCTS IN PERUVIAN AMAZON - GARCÍA DÁVILA, Carmen Rosa (2017)
Were generated and deposited in Genbank Nucleic acid sequences of the COI gene of 207 species of fish commercialized in the human and ornamental markets. Subsequently, the nucleotide sequences were used as a basis for comparison in the specific identification of: i) larvae of catfish collected in three hydrological basins (Ucayali, Napo and Marañón), showing to be a much safer alternative to morphological and morphometric studies; ii) of fingerlings of dubious morphological identity in the export processes, showing that The specific identity of saltón blanco B. filamentosum and santón negro B. capapretum juvenile assigned a priori by the extractors was wrong and iii) subproducts of Amazonian fish, showing the high degrees of substitution in fresh fillets. The generation of these sequences bank allowed us to propose protocols based on molecular characterization of the species, which we think will contribute to the modernization of the system of inspection and monitoring of the commercialization of fish (ornamental and consumer), allowing policy makers greater control both in the area of commercialization and sustained management and conservation in the fishing sector in the Peruvian Amazon.